Radical Scavenging of White Tea and Its Flavonoid Constituents by Electron Paramagnetic Resonance (EPR) Spectroscopy - Nurul Aini, Mohd Azman; Peirò, Sara; Fajari, Lluis; Julià, Luis; Almajano, María Pilar (ACS Publications, 2014)
White tea (WT) presents high levels of catechins, which are known to reduce oxidative stress. WT is the least processed tea, unfermented and prepared only from very young tea leaves. The subject of this paper is the use of the spin trap method and electron paramagnetic resonance (EPR) spectroscopy as the analytical tool to measure, for the first time, the radical scavenging activity of WT and its major catechin components, epicatechin (EC), epicatechin-3-gallate (ECG), epigallocatechin (EGC), and epigallocatechin-3-gallate (EGCG), against the methoxy radical, using ferulic acid as antioxidant pattern. The antioxidant activity has been measured by the decrease of the intensity of the spectral bands of the adduct DMPO−OCHH3 in the EPR with the amount of antioxidant in the reactive mixture. Tea leaves and buds were extracted with waterless methanol. It has been proved that tea compounds with more antiradical activity against methoxy radical are those with the gallate group, EGCG and ECG.